2002
DOI: 10.1002/mus.10277
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases, inhibitor, and acid phosphatase in muscles of immobilized hindlimbs of rats

Abstract: External fixation procedures of limb immobilization provide excellent experimental models to study mechanisms involved in muscle disuse atrophy and recovery. Female Wistar rats (7-8 months old) had their right hindlimbs immobilized by an external fixation procedure for 5, 10, 21, and 30 days. Muscle mass of the gastrocnemius and quadriceps muscles was reduced by 41-46% in comparison with contralateral nonimmobilized legs. Acid phosphatase activities were significantly increased after 21 and 30 days of hindlimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 35 publications
3
54
0
2
Order By: Relevance
“…Recent studies suggest that MMPs play an important role in response to muscle injury and repair (57) and rats under long-term hindlimb suspension have increased MMP2 activity (52). Our studies suggest that MMPs have differential activity in cast-immobilized and tenotomy-treated muscles.…”
Section: Discussionmentioning
confidence: 51%
“…Recent studies suggest that MMPs play an important role in response to muscle injury and repair (57) and rats under long-term hindlimb suspension have increased MMP2 activity (52). Our studies suggest that MMPs have differential activity in cast-immobilized and tenotomy-treated muscles.…”
Section: Discussionmentioning
confidence: 51%
“…The majority of studies regarding skeletal muscle protein degradation during disuse atrophy have focused on three primary proteolytic pathways: the cytosolic Ca 2ϩ -dependent proteolysis (calpains), lysosomal proteolysis (cathepsins), and ATP-dependent proteolysis (ubiquitin-proteasome degradation). Nevertheless, other degradative processes including intracellular and extracellular protease cascades (serine proteases and matrix metalloproteinases) and apoptosis (caspases) are all likely involved in muscle atrophy, though with unclear extents of involvement (86,87). Recent investigations have indicated that the three primary proteolytic systems may work as partners during muscle proteolysis (17,55).…”
Section: 2) Regulation Of Protein Degradationmentioning
confidence: 99%
“…1 Recent studies suggest that matrix metalloproteinase-2 (MMP-2) plays a key role in the response of muscle tissue to various forms of injury and disuse. [2][3][4][5] However, the mechanisms of MMP-2 regulation associated with muscle atrophy remain undefined.…”
Section: Introductionmentioning
confidence: 99%